(untitled) (American Journal of Pedagogical and Educational Research, 2023)
One of the most important things in raising a healthy child is exercise, movement games, and sports entertainment. When exercising with children, it is important to monitor their health, appearance, mood, fatigue, appetite, and sleep. Every healthy child should have a medical examination 2-3 times a year. Natural and individual development of physical abilities that provide the necessary and sufficient level of development of physical qualities, monitor skills and abilities in the child, providing information on general physical education to preschool children, including mental, technological, achieving the acquisition of moral, ethical and aesthetic values, the actualization of knowledge at the level of basic skills of independent study.